Engineering pore morphology using silica template route over mesoporous cobalt oxide and its implications in atmospheric pressure carbon dioxide hydrogenation to olefins - Gupta, Sharad; Ciotonea, Carmen; Royer, Sebastien; Dacquin, Jean-Philippe; Vinod, C. P. (2020)
Highly ordered mesoporous cobalt oxides (denoted as m-Co-KIT-6 and m-Co-SBA-15) with three dimensional and two dimensional pore morphology respectively have been synthesized using 3D KIT-6, and 2D SBA-15 as silica template via nanocasting route. CO2 hydrogenation activity was evaluated for these mesoporous materials under atmospheric pressure conditions. In comparison to nanoparticles of cobalt oxide (Co3O4-nano), mesoporous catalysts showed excellent activity for CO2 hydrogenation due to their higher number of exposed active sites and lower mass diffusion limitations. The ordered mesoporous structure of Co3O4 catalysts favored the chain growth of carbon atoms for the production of C2+ hydrocarbons while Co3O4 nanoparticles showed strong selectivity toward CH4. High selectivity for C2+ (similar to 25%) was obtained for both m-Co-KIT-6 and m-Co-SBA-15 catalysts at 320 degrees C. In addition, the 3D pore structure of m-Co-KIT-6 catalyst exclusively formed more olefins (54.9%) fraction. (C) 2020 Published by Elsevier Ltd.
Keywords: CO2 hydrogenation; Mesoporous CO3O4; Olefin fraction; Pore morphology; Silica hard template